Adaptation of Morus alba and Morus cathayana plants in a different climate and environment conditions in Indonesia - NANANG SASMITA; JHON HARDY PURBA; I GUSTI AYU DIYAH YUNITI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sasmita N, Purba JH, Yuniti IGAD. 2019. Adaptation of Morus alba and Morus cathayana plants in a different climate and environment conditions in Indonesia. Biodiversitas 20: 544-554. Mulberry (Morus alba L. and Morus cathayana Hemsl.) cultivation business as silkworm feed in Indonesia is increasing, considering the benefits of mulberry economically, ecologically and pharmaceutically. This study aimed to determine the mulberry plants adaptation to the ability of life and growth of mulberry cuttings. The research was conducted at three different places i.e.  BPTH Bali, Cianjur Alam Sutra Nursery (West Java) and East Kutai Farming Farm, using Randomized Block Design consisted of mulberry treatments (M. alba and M. cathayana) and three treatments i.e. using Rootone F, Using Organic solution and Control (no added. The results show different growth rates from various regions in Indonesia. Mulberry growth in West Java was the best compared to mulberry which growth in Bali and Kalimantan. The highest live percentage was observed in West Java for M. alba (95%) and M. cathayana (90%), followed by Bali M. alba (85%) and M. cathayana (80%), Kalimantan M. alba (80%) and M. cathayana (75%). The best high parameter of mulberry plant in West Java for M. alba (80cm) and M. cathayana (76 cm), in Bali for M. alba (67 cm) and M. cathayana (76cm), in Kalimantan for M. alba (58 cm) and M. cathayana (50cm). The best mulberry species based on the whole parameter is M. alba in West Java. This means that West Java climate and environmental conditions are good for mulberry cultivation.